How leadership style influences the enterprise sustainability and innovation - Krasniqi, Ibrahim; Jupa, Njomza (Journal of Social Economics Research, 2024)
This paper aims to analyze the influence of leadership types on enterprise innovation, fostering enterprise sustainability and development. The research analyses specific leadership types, approaches, and theories in enterprises with the aim of linking the specific leadership style with enterprise sustainability and innovation. The study was conducted with 100 respondents from different enterprises. During research, both qualitative and quantitative data were used. The primary data were collected through structured questionaries’ and semi-structured interviews. Beside those, a large number of secondary and tertiary data were collected and analyzed in order to compare the results obtained with actual literature worldwide. The SPSS package was used to analyze primary data, and based on the comparison of the results obtained; it is visible that the most commonly applied leadership style by managers and leaders in Kosovan enterprises is democratic leadership, followed by the autocratic leadership. Results have shown that the laissez-faire style has been minimally implemented. It is a final conclusion that autocratic leadership and democratic leadership styles have imposed a positive influence on innovation processes in enterprises, as well as that there is a positive relationship between effective leadership and the presence of innovations in the surveyed enterprise cases. Different leadership styles have different impacts on sustainability, enterprise working culture, and working creativity and innovation, so the article suggests that leaders in enterprises should be able to establish creative thinking that requires innovative ideas and ways for long-term sustainability.